FACTORS ASSOCIATED WITH DIETARY PATTERNS AND BEHAVIORS AMONG STUDENTS IN LIRA UNIVERSITY. A CROSS-SECTIONAL STUDY. - Agang, Akullu Immaculate; Oceng, Amito Freda; Modi, Derick (SJ Insights, 2025)
Background Having poor dietary patterns and behaviors exposes one to a great risk of acquiring some diseases and having some micronutrient deficiencies. University students are the most affected persons. The study aimed to find out the various factors that affect dietary patterns among students of Lira University. Methodology The study employed a descriptive cross-sectional survey to collect data from 200 students using structured questionnaires. Data was collected and analyzed to discern the relationship among the research variables. Descriptive statistical analysis was used to describe the data in univariate analysis and different proportions for categorical data were generated and presented in frequency tables. Results A total of 200 respondents participated in the study. Most of the participants 146(73.4%) were between the ages of 20-25 while 43(21.6%) were between the ages of 26-30. The majority of the respondents 178(89.0%) were not employed, 90(45.0%) respondents had an average financial situation, and most of the respondents 70(35.0%) were sometimes influenced by financial constraints regarding their dietary behaviors. About the availability of foods in the market, 113(56.5%) respondents found the foods to consume available to them in the markets. In terms of ease of finding food options, half of 100(50.0%) respondents found it somehow easy to find food options around 31(65.5%) skipped meals due to financial constraints. Respondents whose stress affected their eating pattern were more likely to have poor eating behaviors, cOR,2.584,95%CI,0.297-3.149, P=0.019, than respondents whose stress didn’t affect their eating pattern. Conclusion The study financial constraints, limited food accessibility, and stress with poor dietary behaviors among Lira University students. Recommendation Establishment of food healthy team educators to offer guidance and health education on healthy feeding behaviors to the university students.